Totality of the Evidence Suggests Prenatal Cannabis Exposure Does Not Lead to Cognitive Impairments: A Systematic and Critical Review - Torres, Ciara A.; Medina-Kirchner, Christopher; O'Malley, Kate Y.; Hart, Carl L. (Frontiers in Psychology, 2020)
Background: Despite limited data demonstrating pronounced negative effects of prenatal cannabis exposure, popular opinion and public policies still reflect the belief that cannabis is fetotoxic. Methods: This article provides a critical review of results from longitudinal studies examining the impact of prenatal cannabis exposure on multiple domains of cognitive functioning in individuals aged 0 to 22 years. A literature search was conducted through PsycINFO, PubMed and Google Scholar. Articles were included if they examined the cognitive performance of offspring exposed to cannabis in utero. Results: An examination of the total number of statistical comparisons (n=1004) between groups of participants that were exposed to cannabis prenatally and nonexposed controls revealed that those exposed performed differently on a minority of cognitive outcomes (worse on less than 3.5 percent and better in less than 1 percent). The clinical significance of these findings appears to be limited because cognitive performance scores of cannabis-exposed groups overwhelmingly fell within the normal range when compared against normative data adjusted for age and education. Conclusions: The current evidence does not suggest that prenatal cannabis exposure alone is associated with clinically significant cognitive functioning impairments.